P16.02: Sognefjord buoyancy bridge: Feasibility and sensitivity analysis. (13th September 2017) - Visser, Wouter; Amico, Fabio; Torsing, Rob; Top, Reinald; Oosterman, Kay; Bhattacharya, Anurag; Bijlaard, Frans S.K.; Yip, Christine
ABSTRACT: This abstract regards the feasibility and sensitivity analysis of the Sognefjord buoyancy bridge. The bridge will be located in Norway, along the coastal highway E39, between Lavik and Oppedal. It is 4.5km long and has an S‐shape which can change depending on the weather and flow conditions. The S‐shape smoothly extends and connects the two part of the coast roads. As an architectural requirements no cable‐stayed bridge or pylons extruding above the deck are allowed. The deck has a width of 24m and an height of about 25m and in its highest point is positioned at 75m above the sea level. It will bear on 22 separate floating pontoons which will be restrained below the sea level by 44 secondary cables linked to two big main cables spanning from coast to coast and having a diameter of around 1.2m. The typical length of the side spans between the pylons is 200m and the simple supported central span has a length of 450m to allow the passing of the ship. There is no other bridge with the dimensions of the Sognefjord bridge which is the most structural challenging buoyancy bridge ever designed. An extensive analysis of the feasibility of the bridge, pontoons and anchoring system has been developed together with a sensitivity analysis of the main parameters which govern and can affect the design. The outcome of the feasibility analysis is positive and the sensitivity analysis shows that the bridge design has quite good margins to compensate for an increase of the loads. Even though future and further analysis need to be run the design and several other evaluations need to be done (connections, second order effects, fatigue, impact loads). our intermediate conclusion is that it is a feasible concept.